2021
DOI: 10.3389/fvets.2021.657816
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Yeast Culture Into Pelleted Total Mixed Rations Improves the Growth Performance of Fattening Lambs

Abstract: There is a growing interest in the use of yeast (Saccharomyces cerevisiae) culture (YC) for the enhancement of growth performance and general animal health. Grain-based pelleted total mixed rations (TMR) are emerging in intensive sheep farming systems, but it is uncertain if the process of pelleting results in YC becoming ineffective. This study aimed to examine the effects of YC supplemented to pelleted TMR at two proportions of corn in the diet on animal performance, feed digestion, blood parameters, rumen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…This phylum was dominated by Christensenellaceae_R-7_group, Butyrivibrio, Ruminococcus , Saccharofermentans , Anaerovorax , Succiniclasticum (Table 8 ; Fig. 2 ), which agree with previous studies 7 , 63 , 68 71 . Christensenellaceae _R-7_group was also found in the rumen of goats and Yak and has a potential role in cellulose degradation 69 , 72 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This phylum was dominated by Christensenellaceae_R-7_group, Butyrivibrio, Ruminococcus , Saccharofermentans , Anaerovorax , Succiniclasticum (Table 8 ; Fig. 2 ), which agree with previous studies 7 , 63 , 68 71 . Christensenellaceae _R-7_group was also found in the rumen of goats and Yak and has a potential role in cellulose degradation 69 , 72 .…”
Section: Discussionsupporting
confidence: 91%
“…1 , 2 ). Similar findings were obtained by Song et al 63 who investigated the effect of yeast supplementation in the diet of lambs on rumen microbiota. Limited information is available about the effect of the microalgae Spirulina and Chlorella on rumen microbiota, and few studies quantified some of rumen bacterial genera using qPCR and concluded that algae supplementation affected the copy number of those genera, which supports our results 28 , 66 , 67 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The pelleting procedure encompasses steam heating and mechanical strain to break complex fiber constituents and boost starch gelatinization, increasing nutrient digestibility and feed slaking [8]. In comparison with the loose TMR, pelleted TMR has been regarded as an expeditious feed form for ameliorating the digestibility and reducing animal diet sorting, which was a practicable strategy to raise fattening ruminants under the intensive feedlot feeding mode [9]. However, roughage ingredients need to be dried and rough pulverized before they can be used in pelleted TMR.…”
Section: Introductionmentioning
confidence: 99%